2014
DOI: 10.1097/md.0000000000000336
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and Serious Adverse Outcomes in Patients with Cardiovascular or Cerebrovascular Disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 32 publications
(66 reference statements)
0
45
1
8
Order By: Relevance
“…Systematic reviews: The literature search revealed two systematic reviews [116,117]. The original studies included in the systematic reviews were of quality ranging from class I to IV.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews: The literature search revealed two systematic reviews [116,117]. The original studies included in the systematic reviews were of quality ranging from class I to IV.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…One systemic review included seven cohort studies and one cross-sectional study with 47-174 patients [116]. The systematic review with meta-analysis of 13 hospital-based cohort studies focussed on stroke (five studies, 860 patients) and mortality (11 studies, 930 patients) [117]. The mean ages in both reviews were between 56 and 79 years; 41-87% of subjects were males.…”
Section: Overview Of the Evidencementioning
confidence: 99%
“…Another possible explanation for the neutral RCT results is that the relationship between OSA and CV risk may not be as strong as previously reported in meta regression analyses of prospective cohort studies (i.e. ~30% increase in CV risk for 10-unit increase in AHI [14][15][16] 72,73 , using algorithms to assess the patterns and cumulative extent of oxygen desaturation in polysomnography pulse oximetry recordings have shown that the overall cumulative night-time burden of hypoxia is more strongly predictive of CV events and CV mortality than is AHI or the frequency of desaturation events. Results from the DREAM clinical cohort study that identified seven distinct polysomnographic phenotypes also support the importance of hypoxic burden rather than AHI in predicting CV outcomes 74 .…”
Section: Central Sleep Apnoeamentioning
confidence: 85%
“…Meta-analyses suggest that OSA is more strongly associated with cerebrovascular than coronary artery events 13,14 , and CV risk is greater in men than women. While the data in patients with co-existing CV disease and OSA are limited, they suggest that the risk is similar for recurrent stroke, myocardial infarction and all-cause mortality 15 . Whilst there is uncertainty regarding the dose response relationship between apnoea-hypopnoea index (AHI) and these various CV outcomes, meta-regression of available studies suggest that it is semi-logarithmic 14,16 .…”
Section: Cohort Studiesmentioning
confidence: 99%
“… 4 The ensuing sympathetic activation, oxidative stress, and inflammatory cytokines are correlated closely with a range of sequelae (ie, hypertension, stroke, cardiovascular disease (CVD), diabetes mellitus, and cancer). 5 11 Moreover, OSA is associated with all-cause mortality. 12 Thus, OSA has become a major challenge for global public healthcare.…”
Section: Introductionmentioning
confidence: 99%